Female adolescent’s understanding and perception of relational bullying behaviour among peers - Assom, Sophia; Mohd Noor, Amelia (Jurnal Pendidikan Bitara UPSI, 2024)
Relational bullying is a type of bullying that harm others by purposeful manipulation and damaging of their peer relationship. Although it is a type of bullying that is prevalent among adolescents, it has not been particularly studied in the context of Malaysian adolescents, despite growing number of empirical studies on bullying behaviour among adolescents in Malaysia. This qualitative study aims to understand the way female adolescents perceive and experience relational bullying among their peers. Five female students age between 13 to 15 years old was selected to participate in semi-structured interview individually. Five distinct themes were identified: a) defining relational bullying, b) normalisation of relational bullying, c) negative impacts of relational bullying, d) predisposed influenced to relational bullying behaviour and e) coping with relational bullying. Based on these themes, The Adolescent’s Relational Bullying Model was developed to further explained its interconnectivity. This study contributes to understanding of relational bullying and offers deeper insights into bullying behaviour among school-going adolescents in Malaysia.